2006
DOI: 10.1073/pnas.0509378103
|View full text |Cite
|
Sign up to set email alerts
|

Imaging cellular signals in the heart in vivo : Cardiac expression of the high-signal Ca 2+ indicator GCaMP2

Abstract: Genetically encoded sensor proteins provide unique opportunities to advance the understanding of complex cellular interactions in physiologically relevant contexts; however, previously described sensors have proved to be of limited use to report cell signaling in vivo in mammals. Here, we describe an improved Ca 2؉ sensor, GCaMP2, its inducible expression in the mouse heart, and its use to examine signaling in heart cells in vivo. The high brightness and stability of GCaMP2 enable the measurement of myocyte Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
415
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 417 publications
(431 citation statements)
references
References 42 publications
10
415
1
2
Order By: Relevance
“…The expression pattern of the sensor protein together with the pharmacological properties of fluorescence transients obtained upon stimulation PF demonstrated that they report PF Ca 2+ transients. These transients have slower kinetics than the actual (volumeaveraged) PF calcium transients because of reporter kinetics [42] and not because of adverse slice conditions as GCaMP2 signals with comparable kinetics have been observed in PFs of living mice [14]. Furthermore, the expression level of GCaMP is low enough as to not buffer the PF Ca 2+ transients to a functionally significant degree because significant Ca 2+ buffering affects PF PPR, and this parameter did not differ between control and GCaMP2 mice.…”
Section: Methodological Considerationsmentioning
confidence: 89%
“…The expression pattern of the sensor protein together with the pharmacological properties of fluorescence transients obtained upon stimulation PF demonstrated that they report PF Ca 2+ transients. These transients have slower kinetics than the actual (volumeaveraged) PF calcium transients because of reporter kinetics [42] and not because of adverse slice conditions as GCaMP2 signals with comparable kinetics have been observed in PFs of living mice [14]. Furthermore, the expression level of GCaMP is low enough as to not buffer the PF Ca 2+ transients to a functionally significant degree because significant Ca 2+ buffering affects PF PPR, and this parameter did not differ between control and GCaMP2 mice.…”
Section: Methodological Considerationsmentioning
confidence: 89%
“…To determine whether TRPV4 sparklets potentiate Ca 2+ release from the ER in PAs, Ca 2+ signals were recorded in PAs from mice that express the Ca 2+ biosensor GCaMP2 selectively in ECs 27, 28. The effect of GSK101 on the activity of Ca 2+ release events and TRPV4 Ca 2+ sparklets was studied by utilizing the differences in kinetics between Ca 2+ release signals from the ER (Ca 2+ pulsars,2, 4 spikes with duration <300 ms, Figure S5A and S5B)4 and TRPV4 Ca 2+ sparklets (discrete, square amplitudes, duration >300 ms, Figure S5A and S5B).…”
Section: Resultsmentioning
confidence: 99%
“…Male C57BL6/J, transgenic GCaMP2 Cx40 , TRPV4 −/− , and eNOS −/− (The Jackson Laboratory, Bar Harbor, ME) mice (10–14 weeks old) were used for all the studies. GCaMP2 Cx40 mice express GCaMP2, a Ca 2+ ‐specific biosensor under the connexin 40 promoter, thereby limiting its expression to only ECs 27, 28. Mice were euthanized with pentobarbital (90 mg/kg; intraperitoneal) followed by decapitation.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, it has been recognised that in some situations circulating 25-hydroxyvitamin D is taken up by extrarenal target cells and acts as a substrate for intracellular 1-a-hydroxylase. This action enables the local production of 1,25-hydroxyvitamin Further information on this area of discussion is available (20,33,(49)(50)(51)(52)(53) .…”
Section: Stratum 7: Cell Functionsmentioning
confidence: 99%